Pan-cancer analysis reveals MTTP as a prognostic and immunotherapeutic biomarker in human tumors - Wang, Wenjia; Gao, Yaping; Liu, Yihan; Xia, Shurui; Xu, Jiayao; Qin, Liwei; Jia, Yongxu; Qin, Yanru (Frontiers in Immunology, 2025)
IntroductionMicrosomal triglyceride transfer protein (MTTP) is an essential lipid transfer protein for the synthesis and secretion of very low density lipoprotein (VLDL) in hepatocytes and chylomicrons (CM) in intestinal cells. Further researches have revealed that MTTP exerted its functions in a variety of tissues beyond the liver and intestine, including the heart, neural tissues and antigen-presenting cells. Dysregulation of MTTP expression can lead to many diseases, such as lipid metabolism disorders, insulin resistance and cardiovascular diseases. Despite its importance, research on MTTP in cancer is limited, with no comprehensive pan-cancer studies available.MethodsMTTP expression was explored with the TIMER 2.0 and Sangerbox databases. The pathological stages and survival analysis of MTTP were analyzed via GEPIA and Kaplan Meier plotter. The gene mutations of MTTP were analyzed by cBioPortal database. The immune landscape of MTTP in the tumor microenvironment(TME) was analyzed using the TIMER 2.0 and single-cell sequencing. Based on the RNA-seq data in TCGA, we constructed GSEA enrichment analysis for MTTP. We identified the pro-tumor and anti-ferroptosis functions of MTTP in gastric cancer (GC) cells by in vitro and in vivo experiments, and analyzed the effect of TME on ferroptosis by single-cell sequencing.ResultsMTTP expression was elevated in at least 1/3 tumors. High expression of MTTP was associated with poor prognosis in most tumors. MTTP levels were significantly correlated with three scores (immune, stromal, and extimate) and immune checkpoints in at least half of tumor types. Single cell sequencing of immune cells showed that MTTP was mainly expressed in macrophages, especially in microglia. MTTP increased in GC and MTTP knockdown limited the proliferation, migration and invasion abilities of GC cells, accompanied by increased sensitivity to ferroptosis. In addition, analyzing the ferroptosis genes associated with MTTP at the single cell level, we found that macrophages may be involved in the ferroptosis process in GC.ConclusionsOur pan-cancer study emphasizes that MTTP is a promising prognostic and immunotherapeutic biomarker in tumors. High expression of MTTP is correlated with the infiltration of diverse immune cells and regulates ferroptosis in GC cells, providing a potential target for tumor immunotherapy.